PELAKSANAAN PROGRAM SANITASI BERBASIS MASYARAKAT DI KOTA PEKANBARU - Habibi Pratama; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the Implementation of Community-Based Sanitation Programs in Pekanbaru City and to find out what factors are inhibiting the Implementation of Community-Based Sanitation Programs in Pekanbaru City. This research was conducted at the Department of Public Housing andPekanbaru City Settlement Area and Lembah Damai Sub-District, Rumbai Pesisir district, Pekanbaru City. As for the theory used in this study is the theory of the program by Charles O. Jones in Suryana namely organizing, interpreting and applying or application. This research uses qualitative research with a descriptive approach using purposive sampling techniques for the community obtained through interviews, observation and documentation. research results show that, the implementation of the Department of Public Housing and Settlement Areas of the City of Pekanbaru on the implementation of community-based sanitation programs in the city of Pekanbaru has been running but has not been maximized. the inhibiting factor is from the community, because many people reject the community sanitation program and the lack of community knowledge about sanitation. it is better to increase socialization to the community so that the community can understand the sanitation-based program and no community refuses to implement the community-based sanitation program. Keywords: Implementation, Sanitation, Program,